Características de carcaça e de carne de suínos alimentados com farelo de algodão e complexo enzimático - Andrade, Rauana Vieira de (2020)
The use of alternative feedstuffs in the pig production has been increased in the Brazilian scenario, due to the price fluctuation of corn and soybean meal that directly impact the production costs, especially in the finishing phase where feed intake is higher. The cottonseed meal is still little used in pig diets due to concerns related to low fiber digestion and utilization by pigs that do not have specific enzymes to degradate fiber that may cause losses to carcass value. Exogenous enzymes have been used increase fiber utilization and, as a consequence, improving the chemical and sensorial quality of pork. The knowledge about the use of cotton industry by-products in pig feeding still is limited regarding its impacts on carcass composition, quality and taste of pork meat. Based on this, the purpose of the present study was to evaluate the carcass characteristics and meat physicochemical and sensorial characteristics of pigs fed increasing dietary levels of cottonseed meal in diets supplemented with enzymatic complex. Dietary inclusion up to 15% of cottonseed in diets supplemented with enzymatic complex did not affect carcass characteristics and meat (Longíssimus lumborum) physicochemical composition of finishing pigs in the present study.